The analysis of synoptic patterns influencing sand and dust genesis over the West Asia region - Saviz Sehat Kashani; مهدی رهنما; Noushin Khoddam; Sara Karami; Abbas Ranjbar (Nīvār)
In order to study the phenomenon of dust in the Middle East, using the reanalyzed data of ERA5 and the observation data of synoptic stations in the period 2009 to 2018, the temporal and spatial patterns of synoptics affecting the formation of dust have been analyzed. With the increase of temperature in spring, a low-pressure is formed in the southeast of Iran, which expands to its northeast in summer, and along with the penetration of a ridge in northeastern Iran, it causes to create pressure gradient and consequently an increase in wind speed. Eventually it causes dust emission. In autumn and winter, the polar jet blows stronger and expands to the south. In summer, however, it becomes weaker and the subtropical jet moves to higher latitudes. In other words, in the warm season of the year, dust storms are accompanied by a strengthening of the pressure gradient near the mean sea level and an increase in wind speed, which activates the sources and emits and transports dust. In the cold season of the year, the formation of the cold front, especially in Iraq, causes strong winds and eventually leads to the emission and transfer of dust.